Study of Criminal Psychology in Indonesian Literature - Ahmadi, Anas (International Journal of Criminology and Sociology, 2022)
This criminal psychology research aims to explore the criminal behavior contained in modern Indonesian literature. This is based on the fact that literature is considered as a creative work that represents elements of criminal behavior that can be viewed from the perspective of criminal psychology. The research method used was qualitative by referring to the interpretation of the text in depth. The data used in the study were literary texts which represent criminal behavior. Data analysis techniques were carried out through the stages of identification, classification, reduction, analysis, exposure, and verification. The result showed that criminal behavior in Indonesian literature is related to corruption, sexual crime, and transnational crime.